Particle number emission rates of aerosol sources in 40 German households and their contributions to ultrafine and fine particle exposure. (31st December 2020) - Zhao, Jiangyue; Birmili, Wolfram; Hussein, Tareq; Wehner, Birgit; Wiedensohler, Alfred
Abstract: More representative data on source‐specific particle number emission rates and associated exposure in European households are needed. In this study, indoor and outdoor particle number size distributions (10–800 nm) were measured in 40 German households under real‐use conditions in over 500 days. Particle number emission rates were derived for around 800 reported indoor source events. The highest emission rate was caused by burning candles (5.3 × 10 13  h −1 ). Data were analyzed by the single‐parameter approach (SPA) and the indoor aerosol dynamics model approach (IAM). Due to the consideration of particle deposition, coagulation, and time‐dependent ventilation rates, the emission rates of the IAM approach were about twice as high as those of the SPA. Correction factors are proposed to convert the emission rates obtained from the SPA approach into more realistic values. Overall, indoor sources contributed ~ 56% of the daily‐integrated particle number exposure in households under study. Burning candles and opening the window leads to seasonal differences in the contributions of indoor sources to residential exposure (70% and 40% in the cold and warm season, respectively). Application of the IAM approach allowed to attribute the contributions of outdoor particles to the penetration through building shell and entry through open windows (26% and 15%, respectively).